MENINGKATKAN KETERAMPILAN DAN HASIL BELAJAR SISWA KELAS XII MIPA-3 PADA MATERI KRITIK SASTRA DAN ESAI MELALUI MODEL PEMBELAJARAN THINK-PAIR-SHARE (TPS) BERBANTUKAN MEDIA AUDIO VISUAL DI SMA NEGERI 1 KEMBANG TANJONG - Juraida Juraida (Jurnal Sosial Humaniora Sigli, 2022)
The objectives of this classroom action research are: (1) to describe the quality of the learning process of writing literary criticism and essay skills through the Think-Pair-Share learning model with audio-visual media for the XII MIPA-3 class students of SMA Negeri 1 Kembang Tanjong; (2) describe the improvement of literary criticism and essay writing skills for class XII MIPA-3 SMA Negeri 1 Kembang Tanjong after learning to listen through the Think-Pair-Share learning model with audio-visual media; and (3) describe changes in learning behavior of students in class XII MIPA-3 SMA Negeri 1 Kembang Tanjong in learning literary criticism and essay writing skills through the Think-Pair-Share learning model with audio-visual media. This study uses a classroom action research design. This classroom action research was carried out in two cycles, namely cycle I and cycle II. Each cycle consists of planning, action, observation, and reflection. The subject of this research is literary criticism and essay writing skills for class XII MIPA-3 SMA Negeri 1 Kembang Tanjong. The results showed an increase in the learning process for listening to short stories through the Think-Pair-Share learning model with audio-visual media. In the first cycle, the students' average score was 75.83 in the sufficient category. The average value in the first cycle has not reached the limit of completeness that has been set by the researcher, which is 75 for each student, so the second cycle is carried out. After the second cycle of action was carried out, the average score of students increased by 86 in the good category. After the formative test was carried out, the results obtained in Cycle I of 30 students who completed 18 students or 60% and those who did not complete there were 12 students or 40%. While in Cycle II of 30 students there were 29 students or 96.6% who completed, and 1 student or 3.3% who did not complete. The behavior of class XII MIPA-3 students of SMA Negeri 1 Kembang Tanjong in learning through the Think-Pair-Share learning model with audio-visual media has changed in a positive direction. In the first cycle of learning, it is known that students have not been active during learning. In the second cycle of learning the students experienced a change in a more positive direction. Students become serious in paying attention to the teacher's explanation so that students can work on the questions easily.Keywords: skills and learning outcomes, Think-Pair-Share model, audiovisual media